The Effect of Halal Labeling, Prices, and Certification on Consumer Interest in Buying MSME Businesses (Case Study: MSME Lazzato Muchtar Basri) - Tara Amriadi; Dahrani Dahrani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The food and drink sector in Indonesia is growing rapidly, fueled by an increasing demand for halal items from Muslim customers. This study aims to evaluate the impact of halal label certification and pricing on consumer interest in buying from Lazzato Muchtar Basri UMKM. The approach used in this research is quantitative, applying an associative research framework. The study focuses on all customers of Lazzato Muchtar Basri UMKM, with a sample of 83 respondents chosen based on the Slovin formula. The approach for collecting data utilized a survey that featured a Likert scale. The results of the study showed that price has a strong influence on consumers' willingness to buy, while halal label certification does not notably impact consumers' purchasing interest. This is shown by the results of the partial test (t-test) related to the price variable, which reveals a value of 0. 001, which is less than zero. At the same time, the pricing and labeling of halal products greatly affect consumers’ willingness to buy these small and medium-sized enterprises (SME) goods. These findings underscore the importance of implementing competitive pricing strategies and obtaining halal certification to enhance the buying interest of Muslim consumers.